The detrimental effects of dirty energy, foreign investment, and corruption on environmental quality: New evidence from Indonesia - Pujiati, Amin; Yanto, Heri; Dwi Handayani, Bestari; Ridzuan, Abdul Rahim; Borhan, Halimahton; Shaari, Mohd Shahidan (Frontiers in Environmental Science, 2023)
The alarming trend of CO2 emissions in Indonesia merits a reinvestigation into the determinants in a bid to conserve the environment. In literature, in Indonesia, three potential determinants, energy, FDI and corruption, have been identified to harm the environment. However, their effects are still undetermined. Thus, this study aims to examine the relationships between corruption (COR), energy use (ENY), foreign direct investment (FDI) and CO2 emissions in Indonesia. The Autoregressive Distributed Lag (ARDL) approach was employed to analyse data for 36 years from 1984 to 2020. The results reveal that corruption contributes to greater environmental degradation in the short run, while FDI does not. However, in the long run, corruption and energy use can positively affect environmental degradation, but FDI can reduce environmental degradation in Indonesia. This study also found two other factors, namely economic growth and urbanisation, that can affect the environment, with mixed findings. These findings are indispensable for policy formulation in Indonesia, as Indonesia is a rapidly developing country that depends on good environmental quality to ensure future growth and sustainable development.